Status of Traditional Chinese Medicine in Greece and its Approach on COVID-19 Pandemic - Grivas Constantinos; Hatzopoulou Anna; Kaparianos Dimitrios; Panagiotaras Taxiarchis; Tzoumerka Vasiliki (Wolters Kluwer Health/LWW, 2021)
Although acupuncture was first introduced to Greece in about 1938, it was not until 1973 that an institution was created to teach it, where its study was limited to medical doctors (MDs). Traditional Chinese medicine (TCM) was not taught to non-MDs until 2004. Even today, TCM has not been integrated into the Greek health system, and in a few exceptions, TCM was mainly associated with pain management. A few private schools teach TCM theory and practice in the fields of acupuncture, moxibustion, herbology, gua sha, and tui na (Chinese massage). This study examines the use of Chinese single herbs and formulas for prevention or treatment during the COVID-19 pandemic in Greece, as well as issues with the availability of Chinese herbs and proposals for substitutes from the traditional Greek medicine point of view.